Tongkonan Social Identity: Families Harmonization on Interfaith Marriage in Toraja (ETNOSIA : Jurnal Etnografi Indonesia, 2019)
Interfaith marriage can be called a meeting of inter-social identities specifically within the context of family. It is therefore an indispensable part of the process for every interfaith marriage couple to de-categorize and re-categorize and consolidate their social identity as a couple so that they can successfully define their new family values. The purpose of this study is to analyze how married couples of different faiths in Toraja harmonize their differences from the perspective of social identity. This study used an ethnographic approach with six informant actors from three interfaith families in Toraja. The results show that these married couples operationalize a dual-hierarchical identity model in an inter-family harmonization effort. Tongkonan identity is placed vertically as a collective identity, while the identity of religion as a person-based social identity is placed horizontally. Both of these have consequences for the emergence of a cross-categorized identity.
Keywords: social identity; interfaith marriage; Tongkonan